Pengukuran Tekanan Darah Sebagai Alat Edukasi untuk Menanggulangi Hipertensi di Masyarakat - Irma Yunawati; Wa Ode Salma; Nurnashrian Jufri; Wa Atiqah; Mirnawati Mirnawati; Lian Eka Fazali; Nevida Sakalo; Hadi Kalisi; Nur Sailan Andani; Radya Permala Dewi (STIKes Ibnu Sina Ajibarang, 2025)
Hypertension is a serious medical condition that can increase the risk of heart disease, stroke, and kidney failure. This study aims to describe the prevalence of hypertension in the Poasia District community, Southeast Sulawesi, as well as the importance of education regarding blood pressure measurement. The method used is descriptive research with a cross-sectional approach, where data is collected through blood pressure measurements in individuals aged 13-65 years. The results showed that of the total individuals examined, there were variations in the cardiovascular health category, with 15 people in the normal category, 10 people prehypertensive, and 15 people experiencing hypertension. The educational program implemented was successful in increasing public awareness about the dangers of hypertension and the importance of regular blood pressure measurements. The conclusion of this research confirms that continuous health education and collaboration between various parties are very important in efforts to prevent and control hypertension in society.